Emerging techniques and technologies in brain tumor imaging - Ellingson, Ben; Bendszus, Martin; Sorensen, A. Gregory; Pope, Whitney B. (Neuro-Oncology, 2014)
Abstract. The purpose of this report is to describe the state of imaging techniques and technologies for detecting response of brain tumors to treatment in the
Gesehen am 16.07.2020